Red Beetroot Juice Phytochemicals Bioaccessibility: an In Vitro Approach - Ivelina Deseva; Magdalena Stoyanova; Nadezhda Petkova; Dasha Mihaylova (Polish Journal of Food and Nutrition Sciences)
Beetroot, the cultivated form of Beta vulgaris subsp. vulgaris, is known for its various beneficial properties but more critical data about its bioactive compounds digestion is needed. In the present research, the bioaccessibility of phytochemicals in freshly prepared red beetroot juice was studied. Changes in total phenolics content, total flavonoids content, contents of betacyanins and betaxanthins, phenolic acids profile as well as the antioxidant activity were monitored before and after simulated gastrointestinal digestion. Several parameters that provide interrelated information about food quality were additionally evaluated, including oxalic acid and individual sugars content, total titratable acidity, and acetylcholinesterase inhibitory activity. Significant loss of contents of total phenolics and flavonoids measured after digestion resulted in the recovery of 27.07 and 36.4%, respectively. The same negative tendency was observed for betalains bioaccessibility. While nearly 27% of betaxanthins were present after the simulated digestion, almost all betacyanins (96.07%) have been lost. The HPLC analysis of phenolic acids of beetroot juice revealed the presence of chlorogenic, caffeic, p -coumaric, and sinapic acids. After digestion, a 2.5-fold higher concentration of chlorogenic acid was found, however caffeic and p-coumaric acids were no longer detected. The results concerning the antioxidant activity of digested juice were inexplicit. According to the DPPH assay, there was a complete recovery of antioxidant activity, while no activity was detected employing the ABTS assay. Following the cupric ion reducing antioxidant capacity (CUPRAC) and ferric-reducing antioxidant power (FRAP), approximately half of the initial activity was retained. Despite the losses, red beetroot remains a valuable source of biologically active substances. Better understanding of their transformation during digestion is further needed.